Identifying Students' Ability and Difficulties in Writing Hortatory Exposition Text :A case study of eleventh graders in a senior high school in Bandung - Fauziah, Nurul Isra (2014)
The background of this study is the need for teachers to know students' real competence and difficulties in writing. Therefore, this study aims to find out students' ability and difficulties in writing Hortatory Exposition text. This study used a qualitative case study design. The main data were six texts written by the students which represent high, middle and low achievers' texts. The texts were analyzed by using Rose's writing rubric (2007) and SFL frameworks proposed by Gerot & Wignell (1994), Eggins (2004), Halliday & Matthiessen (2004), Martin & Rose (2008) and Emilia (2014). The findings show that in terms of schematic structure, the low and middle achievers encounter problems in elaborating the arguments and writing the Recommendation. However, the students have the ability to write Hortatory Exposition text by using appropriate linguistic features with the exception of the grammatical structure in passive voice and complex clauses. Instead of that, textually, the students are capable to use various types of theme and thematic progression to make the text coherence aside from less progress of topic in low achievers' texts. Therefore, considering the findings, it is suggested that the teachers should give more guidance and practice for the students, particularly low and middle achievers in developing the topic and the schematic structure of the text. Keywords: SFL, Transitivity system, Theme system, Hortatory Exposition text. Latar belakang penelitian ini adalah kebutuhan guru untuk mengetahui kemampuan dan kesulitan yang dialami siswa dalam menulis. Penelitian ini bertujuan untuk menganalisis kemampuan dan kesulitan siswa dalam menulis teks Hortatory Exposition. Metode penelitian yang digunakan adalah studi kasus kualitatif. Data utama dalam penelitian ini adalah enam teks yang ditulis oleh siswa-siswa yang mewakili tiga level kemampuan: tinggi, menengah dan rendah. Teks-teks tersebut dianalisis dengan menggunakan rubrik penilaian tulisan Rose (2007) dan teori SFL Gerot & Wignell (1994), Eggins (2004), Halliday & Matthiessen (2004), Martin & Rose (2008) dan Emilia (2014). Hasil penelitian menunjukkan bahwa dalam hal schematic structure, siswa dengan level kemampuan rendah dan menengah kesulitan dalam mengembangkan argumentasi (arguments) dan menulis rekomendasi (Recommendation). Meskipun begitu, para siswa menunjukkan kemampuan untuk menulis teks Hortatory Exposition menggunakan ciri kebahasaan yang tepat, kecuali ketika mereka menggunakan kalimat pasif dan kalimat kompleks. Selain itu, para siswa juga mampu menggunakan berbagai jenis theme dan thematic progression untuk menulis teks yang utuh dan berkesinambungan walaupun siswa-siswa dengan kemampuan rendah masih belum bisa mengembangkan topik tulisan mereka. Berdasarkan hasil penelitian, sangat disarankan bagi para guru untuk memberikan lebih banyak pengarahan dan latihan bagi para siswa terutama siswa dengan kemampuan menegah dan rendah dalam mengembangkan topik dan menulis sesuai struktur teks Hortatory Exposition. Kata kunci: SFL, Transitivity system, Theme system, Hortatory Exposition text